Analisis Penyebab, Konsekuensi, Dan Solusi Potret Kemiskinan Di Kabupaten Mojokerto Pasca Reformasi - Winne Ayunda Gaiska; Naufal Gama Affandyar; Muhammad Yasin (Jurnal Akuntan Publik, 2023)
This study analyzes the causes, consequences and solutions to portrait poverty in post-reform Mojokerto Regency, including: Poverty Line, Number of Poor Population, Percentage of Poor Population, Consequences and Solutions to Post-Reform Poverty. Poverty is a very dynamic problem that depends on the challenges faced. In Indonesia, each government period has its own focus and character in efforts to reduce poverty. Preparing for the analysis requires information to be used in the research process. Information in the form of research published by the Central Bureau of Statistics of Finland (BPS), other information from the BPS of East Java Province, BPS of Mojokerto Regency, using time series data (time series data) at least from the most recent period of 3-5 years, and using djpb data from the Indonesian Ministry of Finance. The results of the study show that the poverty line is known to be directly proportional to the increase in the number of poor people in 2020. This indicates that the increase in the price of food and other staple goods will be far above the average. spending of the poor. The very poor and the poor remained in place, while the near poor became even poorer as their spending could no longer keep up with the rising poverty line. It is hoped that during this reform period, the Mojokerto Regency Government will be able to overcome the impacts and consequences and find solutions or steps to reduce the current poverty problems in Mojokerto Regency.